2020
DOI: 10.3390/smartcities3020022
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Systems Perspective on the Notion of the Smart City

Abstract: This paper focuses on the need for a widened definition of the notion of technology within the smart city discourse, with a particular focus on the “built environment”. The first part of the paper describes how current tendencies in urban design and architecture are inclined to prioritize high tech-solutions at the expense of low-tech functionalities and omits that information and communication technology (ICT) contrasts the art of building cities as an adaptable and habitually smart technology in itself. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Along with the results of regression analysis, multicollinearity was estimated. Multicollinearity exists when two or more predictors in the model are correlated and provide overlapping response information [42]. Multicollinearity was evaluated by variance inflation (VIF) and tolerance considerations.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the results of regression analysis, multicollinearity was estimated. Multicollinearity exists when two or more predictors in the model are correlated and provide overlapping response information [42]. Multicollinearity was evaluated by variance inflation (VIF) and tolerance considerations.…”
Section: Resultsmentioning
confidence: 99%
“…All across history, technology has been an inextricable part of the evolution of cities. In recent years, there has been a change in smart cities' growth pattern, with smart cities seeking to embrace sustainable practices through the use of ICT and other smart solutions [35]. According to previous research, these smart cities have struggled to integrate sustainable development goals into their smart plans, focusing more on achieving competence goals than sustainability objectives and goals.…”
Section: Methodsmentioning
confidence: 99%
“…Hodson & A.Sander (2017), concluded that direct impact of ecological performance on the competitive edge was higher for organizations with lesser HR practices. Moreover, their nding also demonstrated that the organizations with reputable HR practices obtain highly balanced competitive edge through signi cant combination between better ecological and organizational performance (Colding, et al, 2020;Mousa & Othman, 2020). Bongartza, et al (2018), suggested a synergistic integrated model to enhance the contribution of Green SCM and green HRM in transforming organizations to become more sustainable.…”
Section: Green Hrmmentioning
confidence: 98%
“…Accordingly, the penetrating environmental issues (across the world) has driven businesses to adopt several environmental practices, such as, conducting "green and competitive" activities (Jennings & Bamkole, 2019;RenataDagiliūtė, Liobikienė, & Minelgaitė, 2018). In order to achieve green agenda, researchers have proposed that "Human Resource Management" contribute viral part in implanting the green procedures within functions of HRM that could possibly strengthen the organization's sustainability (Colding, et al, 2020;B.Hodson & A.Sander, 2017;Colding, et al, 2020). In a study, Derkzen, Teeffelen, & Verburg (2017) have emphasised that former research has examines the relations between HRM and Intellectual Capital (IC).…”
Section: Introductionmentioning
confidence: 99%